Friday fun Activities impact on team bonding at Indo Rama Synthetics India Limited Butibori Nagpur - Petkar, Rutuja Kailash; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
Friday fun activities play a pivotal role in fostering team bonding, especially in a corporate setting. This study explores the effectiveness of such initiatives at Indo Rama Synthetics India Limited, Butibori, Nagpur, emphasizing their influence on interpersonal relationships, communication, and workplace collaboration. The research utilizes a mixed-method approach, incorporating surveys, interviews, and observational data to assess employee perspectives on these activities. Findings highlight that strategically designed recreational sessions significantly enhance team cohesion, reduce stress, and improve overall morale. Furthermore, the study examines how these initiatives act as a platform for employees to connect beyond formal hierarchies, enabling the cultivation of a more inclusive and cooperative environment. Insights derived also shed light on the potential long-term benefits of sustaining such programs, including increased productivity and employee retention. Recommendations include tailoring activities to employee preferences and incorporating feedback mechanisms to ensure relevance and inclusivity. The paper concludes by advocating for a balanced approach to workplace engagement, where such initiatives complement the organizational goals while fostering a positive and collaborative culture.